Concepts of happiness across time and cultures - Oishi, Shigehiro (2015)
We explored cultural and historical variations in concepts of happiness. First, we analyzed the definitions of happiness in dictionaries from 30 nations to understand cultural similarities and differences in happiness concepts. Second, we analyzed the definition of happiness in Webster’s dictionaries from 1850 to present day to understand historical changes in American English. Third, we coded the State of the Union addresses given by U.S. presidents from 1790 to 2010. Finally, we investigated the appearance of the phrases happy nation versus happy person in Google Ngram Viewer from 1800 to 2008. Across cultures and time, happiness was most frequently defined as good luck and favorable external conditions. However, in American English, this definition was replaced by definitions focused on favorable internal feeling states. Our findings highlight the value of a historical perspective in the study of psychological concepts.